PENERAPAN MODEL SAVI DALAM PEMBELAJARAN MENULIS CERPEN PADA SISWA - Chairul Bachri Bachri Siregar (Universitas Negeri Medan, 2014)
This research is motivated by shortcomings in writing short stories in particular students towrite short stories opposite of events that never happened. It was influenced by the uses of thelearning model. The author provides an alternative model of SAVI for use in teachingwriting. However, previous authors will test the SAVI models to determine the level ofeffectiveness. Based on the research background, this study refers to some formulation of theproblem, namely: 1) How is the ability of class IX students of SMP Negeri 6 Bahorok in learning to write short stories before and after the SAVI models applied in the experimentalclass; 2) How is the ability of class IX students of SMP Negeri 6 Bahorok in learning to write short stories without using SAVI models in the control class; 3) Is there a significantdifference between the ability to write poetry class IX students of SMP Negeri 6 Bahorok inthe experimental class in the control class. The purpose of this study is to describe things that are listed in the formulation of the problem.The underlying theory is a theoretical model of SAVI